Nutritional status and all-cause mortality in older adults with acute coronary syndrome. Issue 5 (May 2020) - Tonet, Elisabetta; Campo, Gianluca; Maietti, Elisa; Formiga, Francesc; Martinez-Sellés, Manuel; Pavasini, Rita; Biscaglia, Simone; Serenelli, Matteo; Sanchis, Juan; Diez-Villanueva, Pablo; Bugani, Giulia; Vitali, Francesco; et al.
Summary: Background & aims: The present analysis investigated the prevalence and the prognostic implication of nutritional status in older adults hospitalized for acute coronary syndrome (ACS). Methods: The analysis is based on older ACS patients included in the FRASER and LONGEVO SCA studies. The Global Risk of Acute Coronary Events (GRACE) risk score was computed in all patients. Nutritional status was assessed with the Mini Nutritional Assessment-Short Form (MNA-SF, normal for values between 12 and 14, at risk of malnutrition for values between 8 and 11, and malnutrition for values ≤ 7). Physical performance was assessed with the Short Physical Performance Battery (SPPB). Primary outcome was all-cause mortality. Results: The study included 908 patients. Overall, 35 patients (4%) were malnourished and 361 (40%) were at risk of malnutrition. After a median follow-up of 288 [187–370] days, the primary endpoint occurred in 94 (10.5%) patients. The mortality rate was 31% in malnourished subjects, 19% in at- risk patients, 3% in patients with a normal nutritional status (p < 0.001). MNA-SF emerged as an independent predictor of all-cause mortality (HR 0.76, 95%CI 0.68–0.84 for single change unit). The MNA-SF score improved the GRACE score's ability to discriminate subjects at risk of death (ΔC-statistic = 0.076, p < 0.001; ΔBIC -28; IDI 0.052, p < 0.001; NRI 0.793, p < 0.001). The prognostic value of MNA-SF was maintained also by including the SPPB score in the predictive model. Conclusion: s: The MNA-SF helped to identify malnutrition in older ACS patients. Moreover, the MNA-SF value is an independent predictor of all-cause mortality and it improves the predictive value of the GRACE risk score.